1981
DOI: 10.1111/j.1600-0897.1981.tb00067.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Anatomical Expression of Transplantation Antigens Within the Normal Human Placental Chorionic Villus*

Abstract: The expression of transplantation antigens by cells of the placenta was examined by immunohistological and immunoprecipitation procedures with defined conventional and monoclonal antisera to beta,-microglobulin, DR and DC gene products, and H-Y antigen. Cells of the mesenchymal stroma within chorionic villi were positive by immunofluorescence for major histocompatibility complex antigens, and in male pregnancies for H-Y antigen, but the trophoblast was consistently negative for all antigen systems examined. Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1983
1983
1997
1997

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Despite the extraembryonic (i.e., non-maternal) origin of these trophoblast membranes and their systemic exposure to the mother's immunocompetent cells, their presence does not cause inflammatory or immunologicai-rejection reactions at their site of sequestration within the lungs (Attwood & Park 1961). Earlier studies, which showed that syncytiotrophoblast membranes do not express major histocompatibility complex (HLA) antigens (Table II), have now been confirmed many times with monoclonal antibodies to HLA framework antigens (Galbraith et al 1981, Sunderland et al 1981a, Johnson et al 1981. Nonetheless, there is IVS •^^x^.^-^^^^i^'zr:' *> ^.…”
Section: Villous Trophoblastmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the extraembryonic (i.e., non-maternal) origin of these trophoblast membranes and their systemic exposure to the mother's immunocompetent cells, their presence does not cause inflammatory or immunologicai-rejection reactions at their site of sequestration within the lungs (Attwood & Park 1961). Earlier studies, which showed that syncytiotrophoblast membranes do not express major histocompatibility complex (HLA) antigens (Table II), have now been confirmed many times with monoclonal antibodies to HLA framework antigens (Galbraith et al 1981, Sunderland et al 1981a, Johnson et al 1981. Nonetheless, there is IVS •^^x^.^-^^^^i^'zr:' *> ^.…”
Section: Villous Trophoblastmentioning
confidence: 99%
“…Nonetheless, one thing is quite clear, the interstitial trophoblast is able to wander at will within uterine tissues, passing as far as the myometrium, seemingly remaining in good health and unimpeded in its journeys (Pijnenborg et al 1981). When knowledge of major histocompatibility complex (MHC) antigens on trophoblast extended only to the syncytiotrophobiast of the chorionic villous, which is MCH-negative (Faulk & Temple 1976, Galbraith et al 1981, some of the supposedly unprecedented findings such as endovascular trophoblast within spiral arteries, interstitial trophoblast in myometrium, etc., could be superficially accepted, and one could feign understanding; because it was assumed that all trophoblast subsets also lacked MHC antigens. Contemporary knowledge indicates that the assumption was quite incorrect; for, not only are Class I antigens found on the endovascular trophoblast, but they are also identified on some interstitial trophoblast (Table II), thus, expanding our knowledge of trophoblast subsets but deepening our ignorance of cellular coexistence mechanisms at the maternotrophoblastic interface.…”
Section: Interstitial Trophoblastmentioning
confidence: 99%
“…Other studies in the human showed that the placenta also carries unique class I, or class I-like, antigens, the TLX antigens (25, 26), and class I molecules that carry only broadly crossreactive public antigenic determinants (27). Class II antigens are absent from the placenta in both the mouse (9, 28) and the human (14)(15)(16)(17)(18)(19) 29) .Studies in the rat demonstrated that during pregnancy the maternal strain in certain mating combinations made an antibody response to the paternal component of the fetal histocompatibility antigens without any prior sensitization (22, 30,31) . The most potent response occurred when the u X a (female X male) haplotypes were mated.…”
mentioning
confidence: 99%
“…Other studies in the human showed that the placenta also carries unique class I, or class I-like, antigens, the TLX antigens (25, 26), and class I molecules that carry only broadly crossreactive public antigenic determinants (27). Class II antigens are absent from the placenta in both the mouse (9, 28) and the human (14)(15)(16)(17)(18)(19) 29) .…”
mentioning
confidence: 99%
“…Simultaneously, the placenta appears to function like an immunologic sink, trapping maternal anti-MHC antigen and organ-spe cific antibody and preventing it from reach ing the fetus [30], Placental cells'such as fibroblasts, Hofbauer cells and blood vessel cells do express fetal MHC antigens [31] and can complex with maternal antifetal MHC antibodies passing through the placenta. In creased immune complex formation on pla cental surfaces as well as in the circulation of women with toxemic pregnancy has been documented [32], Similarly during toxemic pregnancy, the amount of complement com ponents detectable on placental surfaces is more than in normal pregnancy, suggesting amplification of antigen-antibody interaction occurring within the placenta [33].…”
Section: Placental Transport Versus Trapping Of Immunoglobulinmentioning
confidence: 99%